Elasticities and trade imbalances: The significance of the Marshall/Lerner condition - John David Pitchford (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1990)
The Marshall/Lerner condition is examined in a context in which full account is taken of the intertemporal optimizing conditions inherent in the balance of payments. This analysis suggests that the condition has only a very limited significance.
Keywords: 330; Außenwirtschaftstheorie; Monetäre Außenwirtschaftstheorie; Außenhandelselastizität; Theorie